Result of Pallidotomy in Parkinson’s Disease in Nepal - Shrestha, Resha; Taira, Takaomi; Shrestha, Pranaya; Rajbhandari, Pravesh; Dhakal, Sudan; Acharya, Samir; Limbu, Chandra Prakash; Pant, Basant (Nepal Journal of Neuroscience, 2016)
Surgical treatment of Parkinsons disease (PD) has already been an established treatment. Currently pallidotomy, Deep Brain Stimulation (DBS) of Globus pallidus internus (GPi) and Subthalamic nucleus (STN) are available mode of surgical treatment of PD. We have included all patients of idiopathic Parkinosons disease who underwent pallidotomy in Annapurna Neurological Institute and Allied Sciences since 2014. The demographics of the patients have been shown and the patient’s improvement has been shown by Unifi ed Parkinsons Disease Rating Score (UPDRS). We have found that pallidotomy is still a promising surgical modality but it is advised to perform either unilaterally or staged bilaterally with at least 3 months gap inbetween. Nepal Journal of Neuroscience. Vol. 13, No. 2, 2016, Page: 68-72